2020
DOI: 10.5194/egqsj-69-1-2020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term human impact and environmental change in mid-western Ireland, with particular reference to Céide Fields – an overview

Abstract: How to cite:O'Connell, M., Molloy, K., and Jennings, E.: Long-term human impact and environmental change in mid-western Ireland, with particular reference to Céide Fields -an overview, E&G Quaternary Sci. J., 69, 1-32, https://doi.org/10.5194/egqsj-69-1-2020, 2020. Abstract:This paper presents new palaeoecological data from north County Mayo (Co. Mayo), western Ireland, and reviews published data with a view to achieving a better understanding of the timing and nature of early farming in the region, its impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The absence of evidence for a Neolithic landnam is somewhat surprising, especially given that early Neolithic impact is strongly expressed in many Irish pollen records. Landnam may have gone unrecorded in the present instance (~140 y between samples in this part of the profile; each sample integrates ~70 y of pollen deposition) but this seems unlikely given that Landnam events in Ireland are invariably of much longer duration than a century and often result in high P. lanceolata values (can be up to 10% TTP [59,62]; see also profile DYR V below). It is concluded that there was no major early Neolithic farming impact at Ballydoo, which fits in with the lack of archaeological evidence for a local Neolithic presence.…”
Section: Pollen and Related Data Core Bdb Imentioning
confidence: 87%
See 3 more Smart Citations
“…The absence of evidence for a Neolithic landnam is somewhat surprising, especially given that early Neolithic impact is strongly expressed in many Irish pollen records. Landnam may have gone unrecorded in the present instance (~140 y between samples in this part of the profile; each sample integrates ~70 y of pollen deposition) but this seems unlikely given that Landnam events in Ireland are invariably of much longer duration than a century and often result in high P. lanceolata values (can be up to 10% TTP [59,62]; see also profile DYR V below). It is concluded that there was no major early Neolithic farming impact at Ballydoo, which fits in with the lack of archaeological evidence for a local Neolithic presence.…”
Section: Pollen and Related Data Core Bdb Imentioning
confidence: 87%
“…The pastoral farming phase is followed by a period during which human impact is minimal (DYR V-5b; 5-4.17 ka). This presumably corresponds with the lull in farming that is a feature of the late Neolithic in Ireland generally, particularly in western Ireland [59,62]. As regards chronology, the changes recorded in DYR V-5a and 5b are dated to somewhat later (5.65-5 ka and 5-4.17 ka, respectively) than expected on the basis of the generally accepted chronological framework for the Neolithic in Ireland [59,77,78].…”
Section: Derryinver Renvylementioning
confidence: 90%
See 2 more Smart Citations
“…Pollen counts were recorded and calculations were carried out using CountPol version 3.2 (Feeser & O'Connell, 2009). Results were plotted as a series of histograms in a percentage pollen diagram following the format produced at the PRU (O'Connell, Molloy, & Jennings, 2020).…”
Section: Palynological Analysismentioning
confidence: 99%